The Role of ATRA, Natural Ligand of Retinoic Acid Receptors, on EMT-Related Proteins in Breast Cancer: Minireview - Bobal, Pavel; Lastovickova, Marketa; Bobalova, Janette (International journal of molecular sciences, 2021)
The knowledge of the structure, function, and abundance of specific proteins related to the EMT process is essential for developing effective diagnostic approaches to cancer with the perspective of diagnosis and therapy of malignancies. The success of all-trans retinoic acid (ATRA) differentiation therapy in acute promyelocytic leukemia has stimulated studies in the treatment of other tumors with ATRA. This review will discuss the impact of ATRA use, emphasizing epithelial-mesenchymal transition (EMT) proteins in breast cancer, of which metastasis and recurrence are major causes of death.
Keywords: receptory kyseliny retinové; nádory prsu; ATRA; lidé; Humans; Animals; Neoplasm Metastasis; nádorové proteiny; breast cancer; zvířata; protein; Tretinoin; tretinoin; Receptors, Retinoic Acid; ženské pohlaví; Epithelial-Mesenchymal Transition; Female; EMT; Breast Neoplasms; epitelo-mezenchymální tranzice; Neoplasm Proteins; metastázy nádorů